2021
DOI: 10.3389/fcell.2021.645600
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Genetic Landscape of Inherited Retinal Dystrophies

Abstract: Inherited retinal dystrophies (IRD) are a group of diseases characterized by the loss or dysfunction of photoreceptors and a high genetic and clinical heterogeneity. Currently, over 270 genes have been associated with IRD which makes genetic diagnosis very difficult. The recent advent of next generation sequencing has greatly facilitated the diagnostic process, enabling to provide the patients with accurate genetic counseling in some cases. We studied 92 patients who were clinically diagnosed with IRD with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 109 publications
(118 reference statements)
1
20
0
Order By: Relevance
“…In our cohort of achromatopsia patients, we have not observed the c.673+5G>T variant yet. So far, it was only observed once in single heterozygous state in a patient diagnosed with retinitis pigmentosa 35 . This is most likely an incidental finding, as CNGA3 is thought to be primarily involved in cone dysfunction disorders 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of achromatopsia patients, we have not observed the c.673+5G>T variant yet. So far, it was only observed once in single heterozygous state in a patient diagnosed with retinitis pigmentosa 35 . This is most likely an incidental finding, as CNGA3 is thought to be primarily involved in cone dysfunction disorders 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The retina of the human eye is a complex structure that involves the interplay of multiple retinal genes. Over the years, numerous gene mutations have been shown to play a crucial role in retinal dystrophy [ 89 , 90 , 91 ], some of them leading to clinical phase studies for drug development. Studies have shown that most of the genetic mutations associated with RP were due to photoreceptor or RPE dysfunctions (see Table 1 ) [ 92 ].…”
Section: Gene Therapymentioning
confidence: 99%
“…Several high-throughput next-generation sequencing (NGS) technologies using short-read sequencing have accelerated molecular diagnoses for IRD patients, ranging from custom gene panel approaches [5,6] to whole exome sequencing (WES) [7] and whole genome sequencing (WGS) [8,9]. Each technique involves complex outputs to consider in terms of financials, total data generated (and its required storage capacity) and hands-on analysis time per sample.…”
Section: Introductionmentioning
confidence: 99%